Pengaruh Aktivitas Social Media Marketing Terhadap Customer Based Brand Equity Produk Kosmetik Halal Lokal - Niara Ayu Salsabila; Muhammad Akbar Prasetyo (Peneliti.net, 2023)
The purpose of this study was to analyze whether there is an influence from perceived social media marketing activities on brand equity, to analyze whether there is an influence from perceived social media marketing activities to brand experience, and to analyze whether there is an influence from brand equity on brand experience. This data collection by distributing questionnaires. The unit of analysis in this study is individuals, namely individual consumers who have purchased local halal cosmetic products and know the social media of local halal cosmetic products, especially Wardah, Emina, MakeOver, and Something. The data analysis method used by the authors to process survey data distributed to respondents is AMOS version 22 and SPSS version 22. Based on the results of the research that has been carried out, the following conclusions can be drawn: (1) there is a positive influence of perceived social media marketing on brand equity, (2) there is a positive influence of perceived social media marketing on brand experience, (3) there is a positive effect of brand equity on brand experience.